Determinants of perinatal mortality in public secondary health facilities, Abuja Municipal Area Council, Federal Capital Territory, Abuja, Nigeria - Nwokoro, Ugochukwu Uzoechina (Pan Afr Med J, 2020)
INTRODUCTION: in Nigeria, perinatal mortality rate remains high among births at the health facility. Births occur majorly at the secondary healthcare level in Abuja Municipal Area Council (AMAC) of the Federal Capital Territory (FCT). Identifying factors influencing perinatal deaths in this setting would inform interventions on perinatal deaths reduction. We assessed perinatal mortality and its determinants in public secondary health facilities in AMAC. METHODS: delivery and neonatal data from two selected public secondary health facilities between 2013 and 2016 were reviewed and we extracted maternal socio-demographics, obstetrics and neonatal data from hospital delivery, newborns´ admissions and discharge registers. Data were analyzed using descriptive statistics and Cox proportional hazard models (α = 5%). RESULTS: perinatal mortality rate was 129.5 per 1000 births. Asphyxia 475 (34.0%), neonatal infection 279 (20.0%) and prematurity 242 (17.3%) accounted for majority of the 1,398 perinatal deaths. Unbooked status [aHR = 1.8 (95% CI 1.4 - 2.2)], antepartum haemorrhage [aHR = 2.8 (95% CI 1.2 - 6.7)], previous perinatal death [aHR = 2.3 (95% CI 1.7 - 3.1)] and maternal age ≥ 35 years [aHR= 1.4 (95% CI 1.0 - 1.8)] were associated with increased risk of perinatal death. CONCLUSION: perinatal mortality in the studied hospitals was high. Determinants of perinatal death were unbooked antenatal care (ANC) status, antepartum haemorrhage, previous perinatal death and high maternal age. Reducing perinatal deaths would require improving antenatal care attendance with healthcare staff identifying and targeting women at risk of pregnancy complications.